Impact of Digital Transformation on SMEs Operational Efficiency Gain in Nepal - Subedi, Khem Raj; Bhatt, Shankar Datt; Shahi, Min Bahadur; Kharel, Suman (Geographical Journal of Nepal, 2026)
Digital Transformation (DT) is common to facilitate overall efficiency to make optimization of scarce resources and ensure overall efficiency gain business performance. This paper aims to assess the perceived impact of DT on operational efficiency gain of SMEs in Nepal. The study population comprised SMEs that had been operating for at least the past 12 months in Kailali and Kanchanpur districts of Nepal from which samples were selected during first quarter of 2025 through purposive sampling within predefined strata as the cross-sectional survey of 384 SMEs to assess SMEs’ operational efficiency. The findings indicate that digitization level (β = 0.706, p < 0.001), digital payment density (β = 0.287, p < 0.001), efficiency in cost reduction ((β = 0.065, p < 0.001), and size of firm (β = 0.169, p < 0.001) indicating significant contribution on increase in operational efficiency. The estimated model explains 53 percent of the variance in operational efficiency, suggesting a good fit acceptable to the domain of behavioral economics. The findings suggest that digitization is inevitable for enhancing resource optimization and gaining competitive advantage. Based on the findings, policy implication may be suggested as digital capacity building of small enterprises by means of training, affordable digital infrastructure, and technology adoption incentives that can ensure efficiency in operations.